Penilaian Pelaksanaan Kegiatan Pembelajaran di SMK BidangTeknik (Sebuah Kajian Observasi) - Sadrina Sadrina; Muhammad Ichsan M.Nasir (PTE FTK UIN Ar-Raniry, 2017)
Implementation of learning activities in the schools is the responsibility and authority of each school to implement the established curriculum. Assessment is one of the important activities that must be applied in every learning process. Learning is the process of change that occurs in living things. The change in question is a change in behavior and knowledge that occurs in a relatively permanent. Recently, many learning models have been created that aim to create a different learning environment than conventional learning. Schools selected in this research are: SMK AL Mubarkeya, SMKN 2 Banda Aceh, SMK Muhammadiyah Banda Aceh, SMKN 4 Banda Aceh, SMKN Flight, and SMKN 5 Banda Aceh. Based on the results of the above research, it can be concluded that, almost all of the sample studies schools have implemented Curriculum 2013 or K13 properly and perfectly. Almost all schools have implemented creative learning methods, such as problem-based learning, project-based learning, project-based instruction, inquiry and cooperative learning.